Hubungan Kepadatan Hunian dan Pencahayaan Kamar dengan Kejadian ISPA pada Balita di Wilayah Kerja UPTD Puskesmas Babelan 1 - Dita Rahmadanti; Rony Darmawansyah Alnur (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
Acute Repiratory Infections (ARI) is a health problem that occurs due to respiratory infections that attack both the upper and lower respiratory tract and is usually common and mostly experienced by toddlers. Bekasi Regency has the second highest number of cases of ARI among toddlers in 2018 with 560 cases (9.03%) at the Babelan 1 Health Center in the last three years there has been an increase in ARI cases in toddlers aged 12-59 months, in 2020 there were 17 cases increasing in 2021 to 28 cases and increasing to 40 cases in 2022. This study aims to determine the relationship between occupancy density and room lighting with the incidence of ARI in toddlers in the Babelan 1 Puskesmas Working Area. This study used a case control design. The population in this study were all toddlers aged 12-59 months who lived in the Working Area of UPTD Puskesmas Babelan 1 in 2023. The population in the case group consisted of all toddlers who suffered from ARI from January-December 2022 at the MTBS Poly and the control population consisted of all toddlers who had never been reported to have ARI. The sample in this study were 40 cases and 40 controls. This study was conducted from November 2022-July 2023. The results of bivariate analysis showed there was a significant relationship between room occupancy density (pvalue = 0.003) and room lighting (pvalue = 0.006) with the incidence of ARI in toddlers. Mothers with children under the age of five are encouraged to actively consult with healthcare workers during educational sessions. This is aimed at increasing awareness among mothers with toddlers about the importance of considering factors such as family behavior and the physical condition of their homes.